2018
DOI: 10.1016/j.bpj.2018.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Mechanosensitivity of Cancer Cells in Contact with Soft Substrates Using AFM

Abstract: Cancer cells are usually found to be softer than normal cells, but their stiffness changes when they are in contact with different environments because of mechanosensitivity. For example, they adhere to a given substrate by tuning their cytoskeleton, thus affecting their rheological properties. This mechanism could become efficient when cancer cells invade the surrounding tissues, and they have to remodel their cytoskeleton in order to achieve particular deformations. Here we use an atomic force microscope in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 58 publications
5
70
0
Order By: Relevance
“…We found that a grade II (RT112) and a grade III (KU) bladder cancer lines are softer than normal urinary human (NHU) cells at the intracellular scale ( Figure 1A), consistent with previously published results 36,37 . When KIF20A was inhibited, intracellular rigidity decreased in both cell lines ( Fig.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We found that a grade II (RT112) and a grade III (KU) bladder cancer lines are softer than normal urinary human (NHU) cells at the intracellular scale ( Figure 1A), consistent with previously published results 36,37 . When KIF20A was inhibited, intracellular rigidity decreased in both cell lines ( Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Intracellular relaxation experiments of beads trapped by optical tweezers (Fig.1B) allowed us to measure two phenomenological parameters, the rigidity index and the bead step amplitude, and to extract the complex shear modulus using a model based on power law rheology (see Methods). These measurements confirmed that lower grade (RT112) cells are softer than higher grade (T24) cells 36,37 ( Fig. 1B).…”
Section: Bladder Cancer Cells Are Softer Than Normal Urothelial Cellssupporting
confidence: 75%
See 1 more Smart Citation
“…The role of these mechanical changes is not clear yet. Cell contractility and cell stiffness are correlated in muscle cells [63][64][65][66][67] ; fibroblasts 33 and epithelial cancer cells 68 getting stiffer also get more viscous. Although the inner structure of leukocytes differs from these cell types, the increase in stiffness and viscosity that we observe during activation might be a manifestation of conserved cytoskeletal-based properties among mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a mechanotransduction signaling pathway involving actomyosin contractility, focal adhesion kinase FAK and Yes-associated protein YAP has been deciphered in ovarian cancer cells [54 ]. In the context of cancer again, the elastic modulus of bladder cancer cells was shown to increase with substrate rigidity [55 ]. A novel signaling pathway in cell-substrate adhesion-induced mechanotransduction was recently discovered and involves the metabolic sensor AMP-activated protein kinase (AMPK) [56 ].…”
Section: Mechanosensing At Focal Adhesions and Cell-cell Junctionsmentioning
confidence: 99%